Dopaminergic neurons in the paraventricular hypothalamus extend the food consumption phase - Winda Ariyani; Chiharu Yoshikawa; Haruka Tsuneoka; Izuki Amano; Itaru Imayoshi; Hiroshi Ichinose; Chiho Sumi-Ichinose; Noriyuki Koibuchi; Tadahiro Kitamura; Daisuke Kohno (Proceedings of the National Academy of Sciences, 2025)
Feeding behavior is controlled by various neural networks in the brain that are involved in different feeding phases: Food procurement, consumption, and termination. However, the specific neural circuits controlling the food consumption phase remain poorly understood. Here, we investigated the roles of dopaminergic neurons in the paraventricular nucleus of the hypothalamus (PVH) in the feeding behavior in mice. Our results indicated that the PVH dopaminergic neurons were critical for extending the food consumption phase and involved in the development of obesity through epigenetic mechanisms. These neurons synchronized with proopiomelanocortin neurons during consumption, were stimulated by proopiomelanocortin activation, and projected to the lateral habenula (LHb), where dopamine receptor D2 was involved in the increase in food consumption. In addition, upregulated tyrosine hydroxylase (TH) expression in PVH was associated with obesity and indispensable for obesity induction in mice lacking Dnmt3a . Taken together, our results highlight the roles of PVH dopaminergic neurons in promoting food consumption and obesity induction.